Dibutylamine-catalysed efficient one-pot synthesis of biologically potent pyrans. Issue 5 (28th January 2015) - Kalla, Reddi Mohan Naidu; Kim, Mi Ri; Kim, Il
Graphical abstract: Abstract: An expedient, eco-friendly and efficient procedure for the preparation of novel pyran derivatives has been developed through a solvent-free, one-pot reaction of various aldehydes, malononitrile and either methylacetoacetate or ethyl benzoylacetate in the presence of dibutylamine (2.5 mol %) at room temperature. This procedure is advantageous because it is mild, environmentally friendly, gives high yields and requires short reaction times. Furthermore, the product did not necessitate separation via extraction and column chromatography.